Evaluation of patient satisfaction of an outpatient gastroscopy service in an Asian tertiary care hospital - Ahmad Najib Azmi; Wah-Kheong Chan; Khean-Lee Goh (BioMed Central Ltd., 2024)
Background: There are limited published studies on patient satisfaction towards endoscopy from Asian countries. Different methods of evaluation of patient satisfaction may yield different results and there is currently no study to compare results of on-site versus phone-back interviews. Method: On-site followed by phone-back interviews were carried out on consecutive patients attending the outpatient gastroscopy service of University of Malaya Medical Centre between July 2010 and January 2011 using the modified Group Health Association of America-9 (mGHAA-9) questionnaire. The question on technical skill of endoscopist was replaced with a question on patient comfort during endoscopy. Results: Seven hundred patients were interviewed. Waiting times for appointment and on gastroscopy day, and discomfort during procedure accounted for over 90% of unfavorable responses. Favorable response diminished to undesirable level when waiting times for appointment and on gastroscopy day exceeded 1 month and 1 hour, respectively. Satisfaction scores were higher for waiting time for appointment but lower for personal manner of nurses/staff and explanation given during phone-back interview. There was no significant difference in satisfaction scores for other questions, including overall rating between the two methods. Conclusion: Waiting times and discomfort during procedure were main causes for patient dissatisfaction. Phone-back interview may result in different scores for some items compared with on-site interview and should be taken into account when comparing results using the different methods.